GAYA BAHASA JUAL BELI PEDAGANG DI PULAU BUNYU KALIMANTAN UTARA - Jurianto, Jurianto; Mursalim, Mursalim; Rijal, Syamsul (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
This research aims to determine which language styles are used in buying and selling merchants in Bunyu Island. North Kalimantan and to know what language style function is contained in greeting buying and selling merchants in Bunyu Island, Kalimantan North. This research uses qualitative descriptive methods that describe the use of language styles in buying and selling in Bunyu Island market, North Kalimantan. The object of this research is traders and buyers who are doing buy and sell transactions. Data on the use of the language styles of merchants and buyers is obtained through observation. The techniques used in this research are the recording techniques, the reading techniques and the data analysis techniques. The results of this study are (1) the style of the language used in sale and purchase transactions in Bunyu Island, North Kalimantan, the comparative language style, the style of language opposition, the style of association language, and the repetition language style, (2) The function of language style that Contained in the greeting of buying and selling merchants in Bunyu Island, North Kalimantan, namely the function explaining, function strengthening, function animate the Dead object, the function of stimulating the association, the function raises laughter, and functions to garnish.